Why is Public Policy for Affordable Housing in India Changing So Slowly: Explaining Institutional Inertia. (September 2016) - Ram, Padmini; Needham, Barrie
In India, attempts to stimulate a formal market for affordable housing, by privatizing, deregulating and promoting the private sector funding for housing and infrastructure, as an alternative to the provision by the government, have not been very successful. This study offers as an explanation that the intended market did not arise because the new policy did not take into account the existing institutional structure that regulates the (informal) provision of affordable housing. The existing structure relies heavily on clientelism which, in effect, is serving as an alternative to the market. Therefore, just changing the formal institutions of housing and land policy will not necessarily bring about the desired change in the provision of housing. This is illustrated by the case of informal housing in Raipur.